Multi-Temporal Analysis of Haze Problem in Northern Thailand: A Case Study in Chiang Rai Province - Sirimongkonlertkul, Nion; Upayokhin, Preecha; Phonekeo, Vivarad (Agriculture and Natural Resources, 2013)
Time-series data on PM10 (particulate matter less than or equal to 10 μm in size) readings obtained from 13 measurement stations belonging to the Pollution Control Department of Thailand and moderate resolution imaging spectroradiometry (MODIS) and ﬁ re-related data (MOD14) were analyzed. The study investigated the relationships of the haze-and-smoke distribution characteristics and trends with the number of active ﬁ res in the dry season (from January to April) in 2009, 2010 and 2012. The study was conducted at the regional and local levels to investigate smoke and haze dispersion due to burning activities in three neighboring countries and also within Chiang Rai province itself. Various techniques and tools were applied, including methods based on using a geographic information system to produce buffer zones around the Chiang Rai measurement station with an incremental radius of 10 km. The hybrid-single particle Lagrangian integrated trajectory (HYSPLIT) model was also used to investigate the long-range movement of smoke and haze from neighboring areas to the province. The results showed the smoke and haze problem in Chiang Rai was mainly caused by shortrange movement from burning in the open, mostly conducted within the province, within a radius of 50 km from the Chiang Rai monitoring station. The problem was considered as a local one whose impact was enhanced by meteorological and topographical factors resulting in stagnant air conditions which in turn inhibited the vertical dispersion of smoke and pollutants. As a consequence, the accumulation of PM10 level particulate matter gradually increased. There was additional impact from long-range transport from open burning, via southwesterly winds from burning in neighboring countries and provinces as a result of which, the PM10 level in the province was substantially higher.